Macrophage maturation from blood monocytes is altered in people with HIV, and is linked to serum lipid profiles and activation indices: A model for studying atherogenic mechanisms. - Emily R Bowman; Cheryl M Cameron; Brian Richardson; Manjusha Kulkarni; Janelle Gabriel; Morgan J Cichon; Kenneth M Riedl; Yousef Mustafa; Michael Cartwright; Brandon Snyder; Subha V Raman; David A Zidar; et al. (PLoS Pathogens, 2020)
People with HIV (PWH) are at increased risk for atherosclerotic cardiovascular disease (ASCVD). Proportions of vascular homing monocytes are enriched in PWH; however, little is known regarding monocyte-derived macrophages (MDMs) that may drive atherosclerosis in this population. We isolated PBMCs from people with and without HIV, and cultured these cells for 5 days in medium containing autologous serum to generate MDMs. Differential gene expression (DGE) analysis of MDMs from PWH identified broad alterations in innate immune signaling (IL-1β, TLR expression, PPAR βδ) and lipid processing (LXR/RXR, ACPP, SREBP1). Transcriptional changes aligned with the functional capabilities of these cells. Expression of activation markers and innate immune receptors (CD163, TLR4, and CD300e) was altered on MDMs from PWH, and these cells produced more TNFα, reactive oxygen species (ROS), and matrix metalloproteinases (MMPs) than did cells from people without HIV. MDMs from PWH also had greater lipid accumulation and uptake of oxidized LDL. PWH had increased serum levels of free fatty acids (FFAs) and ceramides, with enrichment of saturated FAs and a reduction in polyunsaturated FAs. Levels of lipid classes and species that are associated with CVD correlated with unique DGE signatures and altered metabolic pathway activation in MDMs from PWH. Here, we show that MDMs from PWH display a pro-atherogenic phenotype; they readily form foam cells, have altered transcriptional profiles, and produce mediators that likely contribute to accelerated ASCVD.